Carbon filter layer for respirator derived from acrylic filter felt - Wang, Yuanfeng; Venkataraman, Mohanapriya; Křemenáková, Dana; Hrůza, Jakub; Militký, Jiří (Waste management (New York, N.Y.), 2025)
Pyrolysis emerges as a strategy for handling waste textiles, wherein the conversion of high-carbon-content textile waste into carbonaceous materials facilitates the restoration of its economic value, concurrently mitigating the environmental impact posed by textile waste. The present study fabricated carbon felts for respiratory filter layers through single-step pyrolysis of acrylic filter felts. The advantage of employing conductive carbon felt as a respiratory filter layer is its capability to concurrently serve two functions: filtration and electrical heating for high-temperature disinfection. In order to achieve these two functions, both the respirator body and the embedded electrodes were designed to ensure the reliability of high-temperature disinfection. The breathability and water vapor permeability of the obtained carbon felt were examined to confirm its comfortability as a respiratory filter layer. The results of filtration efficiency and antimicrobial testing indicated that the carbon felt exhibited a filtration efficiency of over 90 % against inhalable particulate matter, while its antimicrobial properties effectively suppressed microbial growth. This method of reutilizing waste textiles maintained consistency in the usage of textiles before and after reuse, simplified the reusing process of waste acrylic fibers, and simultaneously reduced the manufacturing costs of respiratory filters. The designed respiratory filters have the potential for application in settings such as hospitals and virus research institutions.
Keywords: prostředky na ochranu dýchání; Respiratory Protective Devices; vzduchové filtry; dezinfekce; Carbon; Acrylic fibrous waste; Filtration; uhlík; Textiles; Disinfection; textilie; Carbon felt; Resistive heating; filtrace; Air Filters; Respirator filter; Pyrolysis; pyrolýza